Evaluasi Kebijakan Pengendalian Wabah Penyakit Mulut dan Kuku (PMK) pada Hewan Ternak di Kabupaten Gowa - Aiman Sabar Rezeky (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The livestock sector in Gowa Regency, South Sulawesi, has great potential but is often threatened by outbreaks of Foot and Mouth Disease (FMD), which cause significant economic losses. This study aims to evaluate the FMD control policies implemented by the Gowa Regency Government based on William Dunn's six policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The study used a qualitative approach with primary data collected through in-depth interviews with key informants from the Livestock and Animal Health Division of the Gowa Regency Livestock and Plantation Service and supporting data from various literature. The findings show that the FMD control policy is effective in achieving zero cases, but efficiency is hampered by limited medical personnel (only two veterinarians) and operational budget dependence entirely on the Central Government. Vaccine adequacy is a pull sistem (demand-driven) and compensation distribution is carried out fairly. Community responsiveness increased after severe losses, and policy accuracy was considered most optimal in the implementation of biosecurity and sanitation while promoting vaccination. As a recommendation, the Gowa Government needs to recruit contract workers in the field of animal health, allocate funds for the procurement of operational vehicles and equipment to support laboratory facilities, and issue a Regent Regulation that strictly regulates the implementation of biosecurity and livestock housing patterns in high-risk areas.